L’autoexploitation au volant : les camionneurs indépendants espagnols - Pablo López Calle (La Nouvelle Revue du Travail)
This study of self-employed Spanish long-distance truck drivers shows that the legal form of the capital/labour relationship does not imply a significant difference in relations of capitalist exploitation. Salaried work or self-employment constitute both different profitability strategies as well as different ways of obtaining and increasing added value. At the same time, they are clearly rooted in an exploitative relationship. The articles analyses transformations in the Spanish productive model over the past 30 years, viewing them as part of a “cost-based competitiveness” model based on an intensification of work and individualised employment relations. Growth in sectors like logistics and long-haul transportation, along with the figure of the independent long-distance truck driver, are help to analyse this process.